Physicochemical properties, molecular docking and global reactivity descriptors of manganese carbonyl complexes with imidazole ligands - Gungor, Gaye; Dasdan, Dolunay Sakar; Ustun, Elvan; Sahin, Neslihan (SCIENTIFIC PUBL-INDIA, 2019)
In this study, it was investigated that the solution behavior of two carbon monoxide releasing molecules; Mn(CO)(3)(bpy)(N-imidazole)]PF6 (1), [Mn(CO)(3)(bpy)(N-methylimidazole)]PF6 (2) which showed anticancer activity via zetasizer properties such as measuring particle size, electrophoretic mobility and zeta potential as a function of pH and determined the global reactivity descriptors and molecular docking poses via computational chemistry. The activities of molecules in the different pHs were checked by UV/Vis spectrophotometer.
Keywords: Particle size; mobility; zeta potential; molecular docking; global reactivity descriptors; manganese carbonyl; imidazole; CO-RELEASING PROPERTIES; ANTICANCER ACTIVITIES; BASIS-SETS; DFT; Chemistry